High Accuracy Numerical Method of Thin-Film Problems in Micromagnetics (Journal of Computational Mathematics, 2003)
In this paper, a new high accuracy numerical method for the thin-film problems of micron and submicron size ferromagnetic elements is proposed. For the computation of stray field, we use the finite element method (FEM) by introducing a semi-discrete artificial boundary condition [1,2]. In our numerical experiments about the domain patterns and their movement, we can see that the results are accordant to that of experiments and other numerical methods. Our method is very convenient to deal with arbitrary shape of thin films such as a polygon with high accuracy.
Keywords: Thin-film; Micromagnetics; stray field; Semi-discrete artificial boundary condition.